2023
DOI: 10.1093/genetics/iyad075
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide temperature-sensitivity of Polycomb group regulation and reduction thereof in temperate Drosophila melanogaster

Abstract: Epigenetic regulation varies with the environment. In the fruit fly Drosophila melanogaster, environmental temperature can affect chromatin-based gene regulation. Genes regulated by the Polycomb group (PcG) can vary in their transcriptional output in response to changes in temperature, which typically increases with decreasing temperature. Here, we studied temperature-sensitive expression of PcG target genes on a genome-wide scale, as well as temperature-sensitive enrichment of two histone modifications associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…PcG-regulated genes have been shown to evolve through temperature-dependent selection. Studies of different D. melanogaster populations have demonstrated that the temperature sensitivity of PcG target genes has diverged between tropical and temperate regions with reduced plasticity found in populations from temperate regions [20,48]. In addition, variants of the PcG genes themselves have been shown to be under selection in northern temperate populations of D. melanogaster, leading to the evolution of thermal plasticity [21].…”
Section: Discussionmentioning
confidence: 99%
“…PcG-regulated genes have been shown to evolve through temperature-dependent selection. Studies of different D. melanogaster populations have demonstrated that the temperature sensitivity of PcG target genes has diverged between tropical and temperate regions with reduced plasticity found in populations from temperate regions [20,48]. In addition, variants of the PcG genes themselves have been shown to be under selection in northern temperate populations of D. melanogaster, leading to the evolution of thermal plasticity [21].…”
Section: Discussionmentioning
confidence: 99%
“…As the RNA-seq datasets came from different studies, we tested the possibility that the expression differences resulted from external factors like rearing conditions and examined SC expression from RNA-seq of studies where flies were reared in different environmental conditions. In the datasets examined [56][57][58], SC expression shows minimal change in different rearing temperature (Supplementary Figure 15). Additionally, drastic expression divergence of the germlines can be observed in RNA-seq datasets we generated of closely related species reared in the same controlled laboratory condition, including those in the immigrans group and the sister species D. Nevertheless, these expression patterns reveal that despite the essential roles in regulating crossovers, germline transcriptional regulation of many SC genes is highly labile and constantly evolving, echoing their protein and copy number evolution.…”
Section: Poor Regulatory Conservation Of Sc Genes In Both Female and ...mentioning
confidence: 99%